Extraction of Pacitan Sweet Orange Peel Pectin as a Bioadsorbent on the Adsorption Process of Fe Metal in FeCl3 Solution - Nadhifatuz Zalfa Nur Aisyah; Camelia Asiah Putri Anwar; Nurul Widji Triana (Universitas Islam Raden Rahmat, Malang, 2025)
One alternative to treating waste that contains heavy metals is by bioadsorption process from natural materials as adsorbents. In this study, Pacitan sweet orange peel raw material was used as a FeCl3 metal bioadsorbent. This study aims to obtain pectin as a bioadsorbent for Fe metal in FeCl3 solution with the influence of extraction time and temperature on pectin extraction. In this study, pectin was extracted using the direct extraction method with HCl solvent. To prove the characteristics of pectin, FTIR analysis was conducted by observing the C=O group contained in pectin. Atomic Adsorption Spectrophotometer (AAS) analysis was then used to perform pectin adsorption in a FeCl3 solution. The research results show that optimum conditions are achieved at a temperature of 80°C, a contact time of 90 minutes with the addition of a pectin mass of 90 mg obtained an adsorption efficiency of 60.52%. From the isotherm adsorption analysis, Freundlich isotherm was applied to the adsorption of FeCl3 metal with a determination coefficient (R2) of 0.968.